(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2023)
In 2021. European Commission formally called for a fifth industrial revolution (Industry 5.0). Discussions by participants from all over Europe in two virtual workshops organised by Directorate "Prosperity" of Directorate-General for Research and Innovation on 2 and 9 July 2020 resulted in the document "Industry 5.0: Towards a Sustainable, Human-centric, and Resilient European Industry" issued on 4 January 2021.Industry 5.0 recognises the power of industry to achieve societal goals beyond job creation and growth to become a resilient provider of well-being, making production respect the limits of the planet and placing the well-being of industrial workers at the centre of the production process. Industry 5.0 complements the existing Industry 4.0 paradigm as research and innovation drives the transition to a sustainable, human-centred and resilient European industry.Given that technological advances are changing the way value is created, exchanged and distributed, there is an urgent need to design these technologies to support future societal values. The emergence of these changes and the questions closely linked to technological innovation require industry to rethink its position and role in society.The purpose of this article is to analyse the assumptions of Industry 5.0 and compare them with the Industry 4.0 paradigm.